A família Orchidaceae em um fragmento florestal no sul do Rio Grande do Sul, Brasil - Perleberg, Tângela Denise (2009)
Rio Grande do Sul state south region is not well-known as for its forests floristic composition. This work conducted a taxonomic treatment of Orchidaceae species occurring in Morro Quilongongo, a seasonal semi-deciduous forest fragment located in Southeast Slope, in the municipality of Pelotas, Rio Grande do Sul state. The work shows descriptions, identification key and illustrations of the species, complemented with data about habitat, phenology and geographic distribution. Forty species of Orchidaceae were found distributed in 22 genders. The most representative genders in number of species were Oncidium (8 spp.), Acianthera (4 spp.), Anathallis and Specklinia (3 spp. for each of the plants), however, 14 genders (64%) presented only one specie. The most found species, 29 (72%), are epiphyte, 9 of them are frequently observed upon the rocks. Eleven (27.5%) are terrestrial, seven are frequently found occurring in rocks. The number of species in bloom by month varied from 8 to 14. In September and October a larger number of species come into bloom. In April and July a smaller number of species come into bloom. The regions of Rio Grande do Sul which presented the largest number of these species were the Superior Northeast Slope (30 spp.), Central Depression (27 spp.) and Coast (26 spp.). The Orchidaceae flora of the region is not much represented in the consulted herbaria; just only 11 (27.5%) species found in Morro Quilongongo have a representative exsiccate of the region of Pelotas. Therefore, this work contributes to the knowledge of the South region flora of Rio Grande do Sul, providing data that justify the preservation of this area.